2009
DOI: 10.1111/j.1365-2672.2009.04289.x
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric types of chromosome X in bottom-fermenting yeasts

Abstract: Aim:  To determine the structure of the chimeric chromosome X of bottom‐fermenting yeasts. Methods and Results:  Eight cosmid clones carrying DNA from chromosome X of bottom‐fermenting yeasts were selected by end‐sequencing. Four of the cosmid clones had Saccharomyces cerevisiae (SC)‐type and Saccharomyces bayanus (SB)‐type chimeric ends, two had SC‐type ends and two had SB‐type ends. Sequencing revealed that the bottom‐fermenting yeast strains in this study had four types of chromosome X: SC–SC, SC–SB, SB–SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At any rate, it is obvious that array-CGH showed that the genotypes of meiotic segregants possessing both Lg-FLO1 and ILF1 had an increased copy number of the right end of SC-type chromosome VIII. Previous studies 1,2,12 reported that aneuploidy was also observed among bottom fermenting yeast strains. Most meiotic segregants have wort fermentability and are therefore valuable for the brewing industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At any rate, it is obvious that array-CGH showed that the genotypes of meiotic segregants possessing both Lg-FLO1 and ILF1 had an increased copy number of the right end of SC-type chromosome VIII. Previous studies 1,2,12 reported that aneuploidy was also observed among bottom fermenting yeast strains. Most meiotic segregants have wort fermentability and are therefore valuable for the brewing industry.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why signals of the SBtype Chromosome XI left arm of Weihenstephan34/70-1A were missing, seemed to be that SB-type Chromosome XI was missed from the Weihenstephan34/70-1A genome, while chimera-type Chromosome XI (SC left arm -SB right arm) remained. It has been reported that some bottom fermenting yeast strains possess a chimera-type Chromosome Xs (SC left arm -SB right arm, SB left arm -SC right arm) 9,12 . Thus, the reason why the signal of the SC-type Chromosome X right arm of Weihenstephan 34/70-1A was decreased appears to be similar in the case of Chromosome XIs.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have used DNA microarray analysis to document aneuploidy in yeast (12)(13)(14)(15)(16)(17). While draft wholegenome sequences of some strains of S. bayanus have been reported (18,19), these S. bayanus sequences are not perfectly identical to the SB-type sequence present in bottomfermenting yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have used DNA microarray analysis to document aneuploidy in yeast . While draft whole‐genome sequences of some strains of S .…”
Section: Introductionmentioning
confidence: 99%